Analysis of Students' Mathematical Connection Ability in Solving Task of Function - Arifin, Nur; ., Nurjanah; ., Muzammil (KnE Social Sciences, 2024)
This study aims to analyze the student’s mathematical connection ability in topic of function, by using a descriptive qualitative analysis. Twenty-five students of grade 10 from one of the favorite schools in Sukabumi, West Java participated in the study. Data were collected by conducting instruments mathematical connection ability test and a short interview. The result showed that students’ mathematical connections were still in the low category with an average score of 43. Recommendations for future research are suggested, especially in improving students’ ability in mathematical connection by applying learning methods that will enhance their skills. Keywords: function, mathematical connection ability, solving task